ANALISIS PENGUNGKAPAN PSAK 238 TENTANG ASET TAK BERWUJUD - Luh Putu Puji Trisnawati; Michael; Chelsea Diva Antonetta; Jasmine Eirene; Gracia Juliana Sumadi (POLITEKNIK LP3I JAKARTA, 2024)
Intangible assets must be disclosed on Notes to Financial Statement in Financial Report as a form of transparency. The disclosure of intangible assets has its own risks of misclassification, in which company might acknowledge the existence of intangible assets even though the assets lack of qualification for recognition. Proper disclosure of intangible assets based on PSAK 238 can prevent errors in recognition, such as those that occurred in GOTO company. This research aims to determine the compliance of companies in disclosing intangible assets in their financial statements. The study uses a descriptive analysis method, using purposive sampling on subsectors of Software and IT Services that listed on Bursa Efek Indonesia during 2022 - 2023 period. This research showed that the level of company compliance with disclosure of intangible assets in 2022 was 42% for cost method and 68% for revaluation method. During 2023, the level of company compliance increased to 45% for cost method and 70% for revaluation method. It can be concluded that companies in this subsectors, especially companies that used cost method, has not comply fully with the disclosure requirements for intangible assets under PSAK 238. This research is expected to increase awareness and compliance with the disclosure of intangible assets as regulated in PSAK 238.